Economic spaces of pastoral production and commodity systems markets and livelihoods - Gertel, Jörg; Le Heron, Richard B. (Ashgate economic geography series, 2011)
Pastoralism as a land use system is under recognized in terms of its contribution to food provision and livelihoods as well as to human security.This book is the first attempt to explore the dynamics of economic spaces of pastoral production and commodity systems for explicit South and North positionings. It develops and applies a new approach in combining agri-food, market and commodity chain perspectives with livelihood approaches. This enables new understandings of re-aligning exchange relations between the global south and the global north.
Keywords: Pastoral systems : Economic aspects; Exchange; Commodity exchanges; Human geography; Economic anthropology; Economic geography